Informal settlement upgrading in Cape Town's Hangberg : local government, urban governance and the 'Right to the City' - Fieuw, Walter Vincent Patrick (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2011.